2011
DOI: 10.1007/s10457-011-9385-4
|View full text |Cite
|
Sign up to set email alerts
|

Fruits from shade trees in coffee: how important are they?

Abstract: Agroforestry systems often receive attention and support in the literature for what is perceived as the benefits from multiple products associated with the trees that create the ''forest'' component of the setting. A comparison of small coffee growers' use of fruits derived from the coffee agroforestry holding in Guatemala and Peru reveals that significant differences exist between these groups-not merely in the importance of the fruits themselves, but in the ways they are used. The overall importance of fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 14 publications
1
21
0
2
Order By: Relevance
“…Our work highlights the notion that farmers who increase the prevalence of nitrogen‐fixing leguminous trees will also support more habitat for insectivorous birds, which may increase benefits of pest control and maximize total crop yields by the farm. Although fruit trees provide additional crops to sell and thus resources for the community (Davis, Rice, Rockwood, Wood & Marra, ; Rice ), these short‐term benefits, while potentially beneficial during times of low coffee prices or destructive bouts of weather or disease, may not outweigh the loss of long‐term economic benefits of increased soil nitrogen and biological pest control provided by birds. Needed are studies that identify to what extent particular tree species, or combinations of tree species, influence pest control and subsequent coffee production, and at what scale such species must be used to supply meaningful gains for the farmer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work highlights the notion that farmers who increase the prevalence of nitrogen‐fixing leguminous trees will also support more habitat for insectivorous birds, which may increase benefits of pest control and maximize total crop yields by the farm. Although fruit trees provide additional crops to sell and thus resources for the community (Davis, Rice, Rockwood, Wood & Marra, ; Rice ), these short‐term benefits, while potentially beneficial during times of low coffee prices or destructive bouts of weather or disease, may not outweigh the loss of long‐term economic benefits of increased soil nitrogen and biological pest control provided by birds. Needed are studies that identify to what extent particular tree species, or combinations of tree species, influence pest control and subsequent coffee production, and at what scale such species must be used to supply meaningful gains for the farmer.…”
Section: Discussionmentioning
confidence: 99%
“…Most insect herbivores evolve elaborate physiological, behavioral, and life history adaptations to circumvent the defenses of particular host lineages (Bernays & Graham, ; Tallamy, ); thus, foraging hubs are most often trees that evolved within local food webs. Ironically, coffee growers seeking Bird Friendly© certification increasingly are using introduced shade trees such as Eucalyptus , Mangifera indica , and Citrus (Calviño‐Cancela, ; Méndez, Gliessman & Gilbert, ) because of the additional sources of income provided by lumber (Rice, ) and fruit crops (Ambinakudige & Sathish, ; Rice ). However, these non‐native species are predicted to support few nutritionally valuable insects required by insectivorous birds (e.g., Lepidopteran larvae) because they are evolutionarily novel within tropical ecosystems and thus lack coevolutionary relationships with local insects.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing economic opportunities for growing coffee in the tropics has led to a shift from traditional and sustainable coffee production under shade to unsustainable and habitat-degrading-but high-yieldingsun coffee agriculture (Beer et al 1997;Philpott and Diestch 2003). Consequently, considerable research has been dedicated to the study of shade coffee agroecosystems as landscapes for the conservation of biodiversity such as migratory and resident birds (Robbins et al 1992;Wunderle and Latta 1996;Greenberg et al 1997) and the use of shade tree products for the economic benefit of coffee farmers in places such as Central and South America (Rice 2008(Rice , 2011 and Africa and Asia (Philpott et al 2008;Elliott 2009). In addition, the role of shade trees in microclimate, soil and watershed management in coffee agroecosystems has been well documented (Nair 1989;Lin 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Guatemala, Peru, Costa Rica, and Kenya found musaceous species (bananas and plantains) to be important in agroecosystems with much of the fruit value coming from these species (Albertin and Nair 2004;Elliott 2009;Rice 2011). In Costa Rica musaceous species were grown by 59% of coffee farmers and were among the top eight species reported, while 39 and 58% of farmers reported using these species in Guatemala and Peru, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation